Scientific Literacy in Childhood Education: experience in a countryside school in times of pandemic - Lia Heberlê de Almeida; Elenize Rangel Nicoletti; José Vicente Lima Robaína (Universidade Federal do Norte do Tocantins, 2023)
The present study analyzed the implementation of a set of activities in Early Childhood Education, based on the methodology of the Islands of Rationality (Fourez, 1997). The qualitative research was carried out remotely in two Pre-School classes in a rural school in the city of São Gabriel/RS, during the year 2020. Different methodological strategies were used, such as drawings, observation of the surroundings of their homes, the local landscape, interviews with family members, listening to the radio, writing poems, and producing models. Data are presented according to three categories: i) Reflections on remote work at Escola do Campo; ii) The IIR methodology in Early Childhood Education and iii) Scientific Literacy in Preschool. Remote work brought some challenges, especially in Early Childhood Education, considering the need for interaction between subjects and teacher mediation. It was found that learning took place in other spaces and times, mainly in the interaction with family members and in the observation of the social and natural environments of their surroundings, being important for the construction of the identity of the subject of the countryside and the appreciation of cultures and knowledge. locations. The use of the IIR methodology in Early Childhood Education is in line with the Experience Fields signaled by the National Curricular Common Base (Brasil, 2017). It is concluded that some skills related to Scientific Literacy, such as autonomy, mastery, and communication can be achieved with the development of an IIR in Preschool, even if remotely.